Late-Onset Antibody Deficiency Due to Monoallelic Alterations in NFKB1 - Schröder, Claudia; Sogkas, Georgios; Fliegauf, Manfred; Dörk, Thilo; Liu, Di; Hanitsch, Leif G.; Steiner, Sophie; Scheibenbogen, Carmen; Jacobs, Roland; Grimbacher, Bodo; Schmidt, Reinhold E.; Atschekzei, Faranaz (Frontiers in Immunology, 2019)
Adult-onset primary immunodeficiency is characterized by recurrent infections, hypogammaglobulinemia, and poor antibody response to vaccines. In this study, we have analyzed targeted gene panel sequencing results of 270 patients diagnosed with antibody deficiency and identified five disease-associated variants in NFKB1 in five unrelated families. We detected two single base pair deletions and two single base pair insertions, causing severe protein truncations, and one missense mutation. Immunoblotting, lymphocyte stimulation, immunophenotyping, and ectopic expression assays demonstrated the functional relevance of NFKB1 mutations. Besides antibody deficiency, clinical manifestations included infections, autoimmune features, lymphoproliferation, lymphoma, Addison's disease, type 2 diabetes and asthma. Although partial clinical penetrance was observed in almost all pedigrees, all carriers presented a deficiency in certain serum immunoglobulins and the majority showed a lack of memory B cells (CD19+CD27+). Among all tested genes, NFKB1 alterations were the most common monoallelic cause of antibody deficiency in our cohort.